2022
DOI: 10.2147/ccid.s367763
|View full text |Cite
|
Sign up to set email alerts
|

High Trichophyton violaceum-Induced Tinea Capitis with Isolation of Many Non-Dermatophyte Molds in Scalp Scrapings in Patients Referred to a Dermatology Clinic in Addis Ababa, Ethiopia

Abstract: This work aimed to determine the magnitude of tinea capitis, the diversity and species composition of fungi, and the predominant dermatophytes implicated in causing tinea capitis. Methods: A prospective, cross-sectional study was conducted at a dermatology clinic. Scalp scrapings were collected and cultured, and dermatophyte and non-dermatophyte molds were identified. Results: Of 364 scalp scrapings, fungi were recovered from 301 (82.7%) clinical samples. About 60.7% of the samples were collected from women, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 38 publications
1
1
0
Order By: Relevance
“…The current study shwoed that T. violaceum was the most common causative agent that appeared in 43 (82.7%) positive isolates. This result is consistent with (Bitew, 2022), who showed that T. violaceum is the dominant species among dermatophytes, but it conflicts with the result of Aktas and Yıgıt (Churukian, 2008), who mentioned that it represents only (3.0%). T. violaceum infects skin, hair, and nails causing tinea capitis which is of public health importance because of its transmissibility (Aktas, 2015).…”
Section: Morphological Identificationsupporting
confidence: 86%
See 1 more Smart Citation
“…The current study shwoed that T. violaceum was the most common causative agent that appeared in 43 (82.7%) positive isolates. This result is consistent with (Bitew, 2022), who showed that T. violaceum is the dominant species among dermatophytes, but it conflicts with the result of Aktas and Yıgıt (Churukian, 2008), who mentioned that it represents only (3.0%). T. violaceum infects skin, hair, and nails causing tinea capitis which is of public health importance because of its transmissibility (Aktas, 2015).…”
Section: Morphological Identificationsupporting
confidence: 86%
“…
The research seeks to characterize the toxic secondary metabolites of Trichophyton violaceum and explore their impact in vivo, shedding light on potential implications for human health.This fungus is an anthropophilic dermatophyte that causes a variety of dermatophytosis, most notably tinea capitis, where it infects the hair by an endothrix mode of invasion (Morales, 2019) . Depending on the fungus' metabolic products, the infection's anatomical position, the host's immune system, the virulence of the infecting species, and the microenvironmental variables, tinea capitis can cause moderate to severe inflammation (Bitew, 2022). Transmission of tinea capitis is common between humans and animals.
…”
mentioning
confidence: 99%